In Operando Visualization of Cation Disorder Unravels Voltage Decay in Ni‐Rich Cathodes. Issue 2 (29th September 2020) - Gao, Ang; Li, Xinyan; Meng, Fanqi; Guo, Shengnan; Lu, Xia; Su, Dong; Wang, Xuefeng; Zhang, Qinghua; Gu, Lin
Abstract: Despite the high energy density of Ni‐rich layered‐oxide electrodes, their real‐world implementation in batteries is hindered by the substantial voltage decay on cycling, which mainly originates from bulk and surface structural degradation. Here, in operando observation of cation disorder, a major origin of structural degradation, reveals the voltage decay mechanism in Ni‐rich cathode. Viewed along [1 1–0] and [110] orientations by scanning transmission electron microscopy, it is demonstrated that transition metal (TM) migration gives rise to the drastic fluctuation of interlamellar spacing and NiO bond length, but almost exerts no influence on atom site in ab plane. Density functional theory calculations reveal that the fluctuation of the NiO bond length triggers voltage decay via lifting the energy level of the antibonding (3dz 2 ‐2p)* orbits. Broadening bands by a shorter NiO bond increase the voltage slope of battery, which will reduce the accessible Li capacity within the stable voltage range of the electrolyte. Furthermore, a collaborative path of TM migration triggered by oxygen vacancy is verified to account for the TM migration. The finding provides insights into new chemistry to be explored for developing high‐capacity layered electrodes that evade voltage decay. Abstract : A critical challenge for the commercialization of layer‐structured Ni‐rich cathodes for battery applications is their voltage decay over cycling. Cation disorder during lithium extraction/insertion, a common phenomenon in Ni‐rich cathodes, gives rise to the fluctuation of the NiO bond length. The voltage decay is rooted in the variation of orbital symmetry triggered by the aforementioned lattice symmetry breaking.